The evolution of standards and data management practices in systems biology. Issue 12 (28th December 2015) - Stanford, Natalie J; Wolstencroft, Katherine; Golebiewski, Martin; Kania, Renate; Juty, Nick; Tomlinson, Christopher; Owen, Stuart; Butcher, Sarah; Hermjakob, Henning; Le Novère, Nicolas; Mueller, Wolfgang; Snoep, Jacky; et al.
Abstract : A recent community survey conducted by Infrastructure for Systems Biology Europe (ISBE) informs requirements for developing an efficient infrastructure for systems biology standards, data and model management.